2021
DOI: 10.1007/s10055-021-00575-6
|View full text |Cite
|
Sign up to set email alerts
|

Performance enhancement of facial electromyogram-based facial-expression recognition for social virtual reality applications using linear discriminant analysis adaptation

Abstract: Recent studies have indicated that facial electromyogram (fEMG)-based facial-expression recognition (FER) systems are promising alternatives to the conventional camera-based FER systems for virtual reality (VR) environments because they are economical, do not depend on the ambient lighting, and can be readily incorporated into existing VR headsets. In our previous study, we applied a Riemannian manifold-based feature extraction approach to fEMG signals recorded around the eyes and demonstrated that 11 facial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Some of the sensitive data from the users such as bank/credit card details are acquired when the users make payments. In addition, sensitive data such as biometrics poses/gestures of the users have to be acquired in the metaverse to create digital avatars [32]. Data acquisition helps in training the AI/ML algorithms that can assist in decision making, digital product development, recommendation system development, and marketing in the metaverse [15].…”
Section: Blockchain For the Metaverse: Technical Perspectivementioning
confidence: 99%
“…Some of the sensitive data from the users such as bank/credit card details are acquired when the users make payments. In addition, sensitive data such as biometrics poses/gestures of the users have to be acquired in the metaverse to create digital avatars [32]. Data acquisition helps in training the AI/ML algorithms that can assist in decision making, digital product development, recommendation system development, and marketing in the metaverse [15].…”
Section: Blockchain For the Metaverse: Technical Perspectivementioning
confidence: 99%
“…Considering the study by Abdullah et al (2021), this could also explain the participants' decreased activity to maintain social connectedness and less person-directed gaze in VR conversations compared to videoconferencing. With rapid progress in research on the recognition of facial expressions (Hamedi et al, 2018;Lou et al, 2020;Cha and Im, 2022) and eye movement (Schwartz et al, 2020), as well as their mapping to the avatar, more expressive face and gaze representation will be available in the near future. We expect this to be a crucial facilitator for authentic social exchange in VR.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Therefore, facial electromyography (fEMG), a physiological sensor that is more sensitive to emotions than video-based facial expression analytics, can be used instead. 102 McGhee et al demonstrated that fEMG could accurately distinguish facial expressions and emotional reactions in the virtual world. 103 In summary, measurements from various physiological sensors can be used to understand human cognitive behavior and help in keeping track of the learning progress.…”
Section: Guidelines For Development Andmentioning
confidence: 99%
“…However, in a VR system, the face of the user may be obstructed by a head-mounted VR device, thus limiting the webcam recording of the user’s emotions. Therefore, facial electromyography (fEMG), a physiological sensor that is more sensitive to emotions than video-based facial expression analytics, can be used instead . McGhee et al demonstrated that fEMG could accurately distinguish facial expressions and emotional reactions in the virtual world…”
Section: Guidelines For Development and Deployment Of Vrmentioning
confidence: 99%